2015
DOI: 10.1038/srep17138
|View full text |Cite
|
Sign up to set email alerts
|

Source analysis of P3a and P3b components to investigate interaction of depression and anxiety in attentional systems

Abstract: This study examined the impact of depressive disorders, anxiety disorders and the comorbidity of these disorders on the regional electrophysiological features of brain activity. Sixty-four-channel event-related potentials (ERP) were acquired during a visual oddball task in patients with depressive disorder, patients with anxiety disorders, patients with comorbid depressive and anxiety disorders and healthy subjects. An fMRI-constrained source model was applied to ERP to identify different cortical activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In fact, Long et al [ 40 ] suggest that there is a bidirectional, systematic pattern between the development of depressive and anxious syndromes in young adults. In addition, previous studies [ 41 , 42 , 43 ] have identified similarities in the neurobiology and genetic structure of depression and anxiety. Another possible explanation for the association between depression, anxiety and stress is the fact that they share a significant number of risk factors and symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Long et al [ 40 ] suggest that there is a bidirectional, systematic pattern between the development of depressive and anxious syndromes in young adults. In addition, previous studies [ 41 , 42 , 43 ] have identified similarities in the neurobiology and genetic structure of depression and anxiety. Another possible explanation for the association between depression, anxiety and stress is the fact that they share a significant number of risk factors and symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Due to its effects on affective and cognitive functioning, tVNS could also be of special relevance for clinical research. Several studies have shown that the P3b amplitude is reduced in different mental disorders including, schizophrenia (e.g., Pfefferbaum et al, 1989 ), mood disorders (e.g., Bruder et al, 2009 ; Rongrong et al, 2015 ; Lang et al, 2017 ), or anxiety disorders (e.g., Li et al, 2015 ; Lang et al, 2017 ). This suggests that the P3b amplitude increase through vagus nerve stimulation may reflect symptomatology improvement in patients diagnosed with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This threat-related hypervigilance is a prominent symptom of clinical anxiety, cutting across multiple diagnoses 2 , and these results suggest that it may be mediated by a hyperactive parietal cortex 33,34,36,38,39 . This diminished attention control may explain why (1) individuals with specific phobias may show attentional biases to threatening information [40][41][42][43] , (2) generalized anxiety disorder (GAD) patients have difficulties maintaining attentional focus [44][45][46][47] anxiety interferes with the manipulation of items in working memory 29 . If this is the case, then inhibitory parietal rTMS should also reduce the attention bias to threat seen in anxiety patients.…”
Section: Discussionmentioning
confidence: 99%